2012
DOI: 10.1111/ejh.12014
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant promoter methylation of Dab2 gene in myelodysplastic syndrome

Abstract: The Dab2 gene is inactivated in MDS in part by DNA methylation, and the suppression of Dab2 expression by DNA methylation may play a role in the development of MDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Our study demonstrated that the methylation of Dab2 is common in lung cancers, similar to the reports in other tumors (23,(28)(29)(30). Furthermore, the methylation of Dab2 was correlated with the differentiation, lymphatic metastasis, and TNM stage of lung cancers.…”
Section: Discussionsupporting
confidence: 88%
“…Our study demonstrated that the methylation of Dab2 is common in lung cancers, similar to the reports in other tumors (23,(28)(29)(30). Furthermore, the methylation of Dab2 was correlated with the differentiation, lymphatic metastasis, and TNM stage of lung cancers.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, ectopic expression of Dab2 in several tumor cell lines triggered negative cell growth regulatory properties and tumor suppressive activity of the protein in these cells [22,30]. Downregulation or loss of expression of Dab2 has been correlated with its abnormal promoter hypermethylation [31][32][33][34][35][36] and the presence of inhibitory microRNAs [31,[37][38][39] in human cancers. Despite these findings, additional studies are necessary to better understand the correlation between Dab2 gene silencing and cancer development.…”
Section: Disabled-2 a Putative Tumor Suppressormentioning
confidence: 99%
“…Downregulation or loss of expression of Dab2 has been correlated with its abnormal promoter hypermethylation [31][32][33][34][35][36] and the presence of inhibitory microRNAs [31,[37][38][39] in human cancers. Despite these findings, additional studies are necessary to better understand the correlation between Dab2 gene silencing and cancer development.…”
Section: Disabled-2 a Putative Tumor Suppressormentioning
confidence: 99%
“…Widespread promoter hypermethylation in MDS and secondary AML has been reported by the recent study of Figueroa et al According to this study, bone marrow cells from patients with MDS and secondary AML exhibit an extensive pattern of promoter hypermethylation that differs from normal cells and de novo AML and is not limited with advanced stages of disease. 15 Another gene whose methylation is implicated in MDS pathogenesis is the erythroid transcription factor GATA1, whose upregulation is necessary for erythroid and megakaryocytic development. Methylation of GATA1 in MDS patients inhibits upregulation of the gene and leads to ineffective erythropoiesis.…”
Section: Dna Methylationmentioning
confidence: 99%